2013
DOI: 10.1136/oemed-2012-101135
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and risk of lymphoid and myeloid leukaemia in the European Prospective Investigation into Cancer and Nutrition (EPIC)

Abstract: Our findings suggest a possible role of occupational exposures in the development of both lymphoid and myeloid leukaemia. Exposure to benzene seemed to be associated with both acute and chronic myeloid leukaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Despite the small numbers (four cases and 191 controls), this association was observed for B-cell ALL (OR = 4.38, 95% CI = 1.41 to 13.6), but not for T-cell ALL. Previous studies have also reported an increased risk of NHL in workers in textile-related occupations (23)(24)(25) and of acute myeloid leukemia in those in shoe or other leather goods industries (26). However, there have been no previous reports linking textile and sewing/embroidery occupations with risk of adult ALL.…”
mentioning
confidence: 83%
“…Despite the small numbers (four cases and 191 controls), this association was observed for B-cell ALL (OR = 4.38, 95% CI = 1.41 to 13.6), but not for T-cell ALL. Previous studies have also reported an increased risk of NHL in workers in textile-related occupations (23)(24)(25) and of acute myeloid leukemia in those in shoe or other leather goods industries (26). However, there have been no previous reports linking textile and sewing/embroidery occupations with risk of adult ALL.…”
mentioning
confidence: 83%
“…[111][112][113] In particular, the ad hoc JEMs created by P Stewart 15,16,[101][102][103][104][105] are a hybrid between a job-exposure matrix and expert raters' assessment. They were based both on the literature and industrial hygienists' experience.…”
Section: Ad Hoc Matricesmentioning
confidence: 99%
“…112,113 Various pesticide definitions were used in these matrices. They were sometimes considered as a generic group, 91,94,99,100,[106][107][108][109][110]112 were classified in functional groups (H/F/I), [14][15][16]92,93,96,[101][102][103][104][105]111,113 or were identified at the active ingredient level. 95,98 The occupations concerned were detailed very precisely in some studies.…”
Section: Ad Hoc Matricesmentioning
confidence: 99%
See 2 more Smart Citations